Outcomes of Arthroscopic Latarjet Procedure for Anterior Glenohumeral Instability in Patients With Epilepsy: A Case-Control Study. Issue 3 (March 2022) - Dzidzishvili, Lika; Calvo, Claudio; Valencia, María; Calvo, Emilio
Background: Unacceptably high rates of redislocation, reoperation, osteoarthritis, and coracoid nonunion have been reported in patients with a seizure disorder after surgery for shoulder instabilitiy. Purpose: To evaluate the objective and subjective functional and radiologic results of the arthroscopic Latarjet procedure for anterior shoulder instability in patients with epilepsy and compare them with the results of patients without epilepsy. Study design: Cohort study; Level of evidence, 3. Methods: A retrospective and comparative case-control analysis of patients operated for shoulder instability with arthroscopic Latarjet was conducted. Nineteen patients (21 unstable shoulders) with a seizure disorder (epilepsy group) were matched with 21 patients without a history of seizure (control group). Demographics, surgical indications, and imaging data were collected. Clinical outcomes at a minimum 2 years of follow-up (range, 2-9 years) postoperatively included Rowe score, Western Ontario Shoulder Instability Index (WOSI), Constant-Murley Shoulder Outcome (CMSO) score, and Single Assessment Numeric Evaluation (SANE). The incidence of complications, recurrent instability, redislocation, revision surgery, repeated seizure(s), and presence of osteoarthritis, coracoid nonunion, and osteolysis were also examined. Results: After a mean follow-up of 4.5 years, no significant differences in functional results were found between patients with and without epilepsy on the average Rowe ( P = .917), WOSI ( P = .621), CMSO ( P = .600), and SANE ( P = .859) scores. A total of 5 patients (7 shoulders) continued to have seizures postoperatively, but no seizure-related glenohumeral instability was documented. One dislocation and 1 subluxation were documented while participating in sports in each study group, comprising a recurrence rate of 9.5%, but no significant differences were found at comparison ( P = .605). A bone defect did not influence the results, as no significant difference was found between the 2 groups. Osteoarthritic changes of the glenohumeral joint were observed in 5 shoulders (23.8%) in the epilepsy group and in 3 (14.3%) in the control group ( P = .451). No case of coracoid nonunion or osteolysis was recorded. There was no statistically significant difference in postoperative athletic activity ( P = .660). However, patients with epilepsy had significantly lower pre- and postoperative sports participation ( P < .001). Conclusion: Arthroscopic Latarjet stabilization can lead to improved functional and subjective outcomes and should be considered in patients with epilepsy with recurrent anterior glenohumeral instability. These results can be achieved regardless of the presence of bone defect and the postoperative control of seizures and are similar to those in patients without epilepsy.